Evolution of the monitoring and evaluation strategies to support the World Health Organization's Global Programme to Eliminate Lymphatic Filariasis. (22nd December 2020) - Lammie, Patrick J; Gass, Katherine M; King, Jonathan; Deming, Michael S; Addiss, David G; Biswas, Gautam; Ottesen, Eric A; Henderson, Ralph
Abstract: The Global Programme to Eliminate Lymphatic Filariasis (GPELF) was established with the ambitious goal of eliminating LF as a public health problem. The remarkable success of the GPELF over the past 2 decades in carrying out its principal strategy of scaling up and scaling down mass drug administration has relied first on the development of a rigorous monitoring and evaluation (M&E) framework and then the willingness of the World Health Organization and its community of partners to modify this framework in response to the practical experiences of national programmes. This flexibility was facilitated by the strong partnership that developed among researchers, LF programme managers and donors willing to support the necessary research agenda. This brief review summarizes the historical evolution of the GPELF M&E strategies and highlights current research needed to achieve the elimination goal.